Physician-assisted suicide in Italy: where do we stand and where do we want to go? - Turillazzi, Emanuela; Morena, Donato; Iacoponi, Naomi; Fineschi, Vittorio (Frontiers in Psychiatry, 2025)
Physician-assisted suicide (PAS) remains a subject of global debate and ethical controversy, alongside other end-of-life issues such as euthanasia, palliative care, access to health and social care services, and, importantly, patient autonomy. Within this context, PAS is defined as the practice in which a physician, at the explicit request of a competent patient, prescribes a lethal medication that the patient may self-administer to end their own life. This definition clearly distinguishes PAS from euthanasia, wherein the physician directly administers the life-ending drug. Despite ongoing efforts to establish a unified definition, significant variability remains across jurisdictions with regard to eligibility criteria, procedural safeguards, and the overarching legal and ethical frameworks governing PAS. In Italy, there is currently no effective legislation regulating euthanasia or PAS, which remain practices punishable under Articles 579 (homicide of a consenting person) and 580 (instigation or assistance in suicide) of the Italian Criminal Code. The Tuscany Region has prepared a regulatory attempt at the regional level, which has, however, limited itself to proposing an operational protocol that distinguishes the operational responsibilities that the PAS procedure applicant will face. However, following several relevant cases that profoundly influenced the Italian debate, significant attention has been directed toward end-of-life issues.